Cyclic Voltammetry of Oxygen Reduction Reaction Using Pt-based Electrocatalysts on a Nafion-bonded Carbon Electrode for Direct Ethanol Fuel Cell - Pramanik H.; Basu S. (My University, 2025)
Oxygen reduction reaction (ORR) on Pt-based electrocatalysts in a low-temperature fuel cell like a direct ethanol fuel cell (DEFC) is a big challenge to the researcher because of slow oxygen reduction kinetics at the cathode. The oxygen reduction reaction was studied in acid medium (0.5 M HClO 4 solution) using cyclic voltammetry (CV) with a three-electrode cell assembly (half-cell), an electrochemical device. The electrodes were prepared by dispersing the required quantity of Pt-Ru (40:20% by weight)/C, or Pt-black (HSA) or Pt (40% by weight)/C electrocatalyst, activated carbon and a mixture of Nafion® ionomer (SE-5112, DuPont) and PTFE dispersion. The electrocatalyst loading on each electrode varied from 0.5 to 1.5 mg cm -2. All of the CV experiments were performed at a temperature of 40°C. The CV experiment shows that Pt-black high surface area is very electroactive towards the oxygen reduction reaction compared with Pt/C and Pt-Ru/C electrocatalysts. The loading of 1.0 mg cm -2 of Pt-black high surface area shows the highest current density peak with low activation losses in CV experiments. Similar trends were observed in DEFC experiments with a maximum power density of 10 mW cm -2. Furthermore, ORR on Pt-black HSA takes place by a multi-electronic charge transfer process following a four-electron mechanism. © 2011 Copyright Indian Institute of Chemical Engineers.